Data-driven collision risk assessment to redefine no-fly zone boundaries around aerodromes - Tan, Qian Yi (Nanyang Technological University, 2022)
This report aims to study the efficiency of current No-Fly Zones (NFZs) for Unmanned Aerial Vehicles (UAVs) around aerodromes, in terms of the suitability of their size and geometry. It is proposed that the NFZ geometry around aerodromes should be similar to the aerodrome’s runway(s), due to the expectation that low-flying aircraft occupying the same elevation as a commercial or civilian UAV will be either taking off or landing on a runway, thus a higher risk of UAV-manned aircraft collision exists near the runways. This is investigated by assessing the expected level of safety for UAV flights around Singapore Changi Airport though a data-driven approach. Manned aircraft flight data is obtained from the OpenSky Network (OSN). By comparing the flight density at various points within the current NFZ around WSSS, areas with dense low-flying manned aircraft traffic and a high expected collision frequency will be classified as a critical area, where UAVs may encounter manned aircraft. Around the critical area, an additional buffer area is included to provide time to execute mitigation measures to prevent a UAV from reaching the critical area. Together, the critical area and buffer area make up a Keep-Out Zone, or the proposed NFZ. It was found that based on collision risk alone, the current NFZ around Changi Airport is not efficient in its use of space. It can be resized to be less wide but longer, and reshaped into a rectangular form.